1995
DOI: 10.1073/pnas.92.8.3185
|View full text |Cite
|
Sign up to set email alerts
|

Residue replacements of buried aspartyl and related residues in sensory rhodopsin I: D201N produces inverted phototaxis signals.

Abstract: Residue replacements were made at five positions and in the Halobacterium salinarium phototaxis receptor sensory rhodopsin I (SR-I) by site-specific mutagenesis. The sites were chosen for their correspondence in position to residues of functional importance in the homologous light-driven proton pump bacteriorhodopsin found in the same organism. This work identifies a residue in SR-I shown to be of vital importance to its attractant signaling function: Asp-201. The effect of the substitution with the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…The channel became constitutively open in the dark, whereas illumination caused it to close. A similar inversion of protein function was previously observed in haloarchaeal sensory rhodopsin I (SRI), in which a single point mutation either of the photoreceptor itself or of its cognate transducer converted SRI from an attractant to a repellent photoreceptor (16,17). The SRI inversion is attributable to a switch in its conformation from the C (retinylidene Schiff base accessible from the cytoplasm) to E (Schiff base accessible from the extracellular space) conformer (18)(19)(20).…”
Section: Discussionmentioning
confidence: 77%
“…The channel became constitutively open in the dark, whereas illumination caused it to close. A similar inversion of protein function was previously observed in haloarchaeal sensory rhodopsin I (SRI), in which a single point mutation either of the photoreceptor itself or of its cognate transducer converted SRI from an attractant to a repellent photoreceptor (16,17). The SRI inversion is attributable to a switch in its conformation from the C (retinylidene Schiff base accessible from the cytoplasm) to E (Schiff base accessible from the extracellular space) conformer (18)(19)(20).…”
Section: Discussionmentioning
confidence: 77%
“…Oxidation Procedure and Western Blot Analysis-Membranes were isolated from sonicated stationary phase cells as described (24) and suspended in 4 M NaCl, 25 mM Tris-HCl, pH 6.8. Membrane samples in sonication buffer (4 M NaCl 25 mM Tris, pH 6.8); low salt membrane dilution buffer (250 mM KCl, 20 mM Tris-HCl, pH 8.0), which previously has been shown to maintain HtrI and SRI in a molecular complex as assessed by spectroscopic criteria (7); and all other solutions were allowed to equilibrate to reaction temperature (10 or 25°C) prior to mixing.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was found that certain substitutions at either of two positions in SRI, Asp-201 and His-166, result in inverted (i.e. repellent) responses to orange light (24,30). Three SRI mutants that mediate inverted responses to orange light (D201N, H166A, and H166Y) and one that eliminates phototactic responses to orange light (H166R) were expressed together with HtrI I64C in Pho81Wr…”
Section: Phototaxis Responses Of Cysteine-substituted Htri Mutants-mentioning
confidence: 99%
“…These mutations occur at the positions equivalent to Ala 117 and Gly 120 on TM helix 3 and Leu 266 on TM helix 6 of Rho, respectively. In addition, in the seven TM phototaxis receptor, sensory rhodopsin I, the D201N mutation converted the normally attractant signal of orange light to a repellent signal (24).…”
Section: Fig 4 Light-independent G T Activation By a Set Of Glymentioning
confidence: 99%